A 5-year multidisciplinary care outcomes in children with wilms' tumour managed at a tertiary centre: A retrospective observational study - Felix M Alakaloko; Adeseye M Akinsete; Justina O Seyi-Olajide; Adedayo O Joseph; Olumide O Elebute; Oluwaseun A Ladipo-Ajayi; M Olatokunboh Odubanjo; Omodele A Olowoyeye; Adesoji O Ademuyiwa; Edamisan O Temiye; Adebola A Akinsulie; Christopher O Bode (Wolters Kluwer Medknow Publications, 2022)
Background: Over the last two decades, there has been significant improvement in the outcomes of children with Wilms' tumour (WT) in high income countries (HICs) with approximately 85% survival rate globally. This is partly attributable to a multi-disciplinary team approach to care and the evolution of more robust treatment measures. A previous review in our centre prior to multi-disciplinary team shows a survival rate of 31.48%, However, the survival rates from low- and middle-income countries are still low when compared to HICs due to delays in access to care at all levels, poor to non-existent health insurance coverage, limited workforce resources, weak health-care systems and infrastructure. The aim of this study is to determine the impact of a multi-disciplinary team approach on the treatment outcomes of children with WT. Methodology: This is a 5-year retrospective review of all patients managed with WT at the Lagos University Teaching Hospital, Lagos, Nigeria. Information was extracted from the patients' case notes, operation notes and ward admission records. The data were analysed with SPSS 25, and P < 0.05 was considered to be statistically significant. Results: Forty patients were included in the study; male to female ratio was 1.6:1. The disease occurred in the right kidney in 23 patients (57.5%) and on the left in 17 patients (42.5%). The average duration of symptoms before presentation was 3.6 months (range 1-7 months), majority of patients presented with abdominal masses and were assessed as per unit protocol with abdominal Computerized tomography scan, chest X-ray and abdominal ultrasound scan to assign the patient International Society of Paediatric oncology regimen. The predominant stage at surgery was Stage III 26 (65%), while Stage IV was 9 (22.5%). Morbidity after chemotherapy was 10 (25%). Twenty-five patients (63%) completed chemotherapy while 15 patients (37%) started chemotherapy but defaulted midway. The 5-year survival rate was 75%. Increasing age and male sex were associated with reduced odds of mortality; however, this was not statistically significant. Increased duration of treatment, being treated with chemotherapy alone, as well as advanced tumour stage and histology were associated with increased odds of mortality, however, this was not statistically significant. Conclusion: The development of an institutional WT treatment pathway involving a multidisciplinary team has resulted in improved outcomes. There is need for increased community awareness to improve the time to presentation.